1996
DOI: 10.1029/95ja03516
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of nightside precipitation

Abstract: Considerable information on the state of the magnetosphere is embedded in the structure of nightside charged particle precipitation. To reduce ambiguity and maximize the geophysically significant information extracted, a detailed scheme for quantitatively classifying nightside precipitation is introduced. The proposed system, which includes operational definitions and which has been automated, consists of boundary 1, the “zero‐energy” convection boundary (often the plasmapause); boundary 2e, the point where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
302
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(310 citation statements)
references
References 50 publications
8
302
0
Order By: Relevance
“…The UV-intensity curves tend to be more peaked than the total flux curves. The most equatorward boundary of the DMSP precipitation categorization system is the zero-energy convection boundary (le, i) [Newell et al, 1996]. As zeroenergy particles do not curvature or gradient drift, the Earthward edge of their drift trajectories is controlled purely by the E x B drift.…”
Section: Description Of the Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV-intensity curves tend to be more peaked than the total flux curves. The most equatorward boundary of the DMSP precipitation categorization system is the zero-energy convection boundary (le, i) [Newell et al, 1996]. As zeroenergy particles do not curvature or gradient drift, the Earthward edge of their drift trajectories is controlled purely by the E x B drift.…”
Section: Description Of the Data Setmentioning
confidence: 99%
“…The 5pol marks the poleward boundary of the discrete oval (excluding the diffuse zone observed occasionally poleward of 5e and 5i). For more details about the boundary definitions, see Newell et al [1996]. At 5pol the precipitating energy flux of either electrons (Se) or ions (5i) typically drops by about an order of magnitude within _< 2 ø in magnetic latitude.…”
Section: Description Of the Data Setmentioning
confidence: 99%
“…As noticed by Newell et al (1996), the use of the same terms to describe the precipitation patterns observed by di erent instruments can often lead to disagreement in the interpretation. In this paper we use the terms`d iscrete aurora'' and``discrete auroral arcs'' to describe well-isolated narrow (>100 km) auroral forms having a well-de®ned border corresponding to the low-altitude edge of the form.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion on the sources of auroral precipitation has a long history (see e.g. the reviews by Feldstein and Galperin, 1985;Galperin and Feldstein, 1991;Feldstein and Elphinstone, 1992;Weiss et al, 1992;Elphinstone et al, 1995;Newell et al, 1996). All authors generally agree that the source region of the di use aurora is the inner, near-Earth plasma sheet; it is the origin of the discrete auroras that is a main subject of discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Results bear evidence for a strong connection between solar variability, the state of the magnetosphere, and the chemical climatological state of the middle and lower atmosphere. Newell and Meng (1992) and Newell et al (1996) discuss the morphology of nighttime precipitation and introduce a detailed scheme for quantitatively classifying the radiation belt impact in the low ionosphere. Assessment of radiation belts particle precipitation is useful for not only aeronomy but also lightning-related wave propagation research.…”
Section: Sources Outside the Cavitymentioning
confidence: 99%